MENINGKATKAN MINAT MEMBACA ANAK MELALUI BIMBINGAN BELAJAR DENGAN METODE CERIA (CERITA, EKSPRESIF, RANGSANG IMAJINASI, INTERAKTIF) DI DESA TENIGA - Bilbina, Cahyani Tri; Jurnal Wicara; Fajriah, Utari; Oktaryanti, Jupnanita; Julianti; Sakila, Nur; Maharani, Ni Komang; Hasanah, Hasmiatun; Haekal, Muhamad; Pratama, Cesar Diaz; Anggara, I Made Agusto Dwi (Universitas Mataram, 2025)
The low reading interest among children in rural areas such as Teniga Village, North Lombok Regency, poses a serious challenge in strengthening literacy culture in the aftermath of the 2018 natural disaster. This article discusses the implementation of the CERIA method (Storytelling, Expressive, Imagination Stimulation, Interactive) in a non-formal tutoring program conducted by students of the Community Service Program (KKN) from the University of Mataram. The method is designed to create a joyful, active, and contextual learning atmosphere through approaches based on storytelling, creative expression, imagination stimulation, and interactive activities. The program was carried out over four weeks at Taman Pecatu (Pecatu Park) and local elementary schools, with the active participation of school-aged children. Evaluation results indicated a significant increase in attendance, children’s engagement, as well as their ability to produce literacy works such as rhymes, poems, and speeches. The program achieved an average success rate of 82.6%, demonstrating that the CERIA method is effective in enhancing children’s reading interest. Therefore, this approach is recommended for application in other regions facing similar literacy challenges.